RNAi-mediated silencing of Mediterranean fruit fly (Ceratitis capitata) endogenous genes using orally-supplied double-stranded RNAs produced in Escherichia coli - Ortolá, Beltrán; Urbaneja, Alberto; Eiras, Marcelo; Pérez-Hedo, Mertixell; Daros, José A. (Wiley Online Library, 2023)
BACKGROUND: The Mediterranean fruit fly (medfly), Ceratitis capitata Wiedemann, is a major pest affecting fruit and vegetable production worldwide, whose control is mainly based on insecticides. Double-stranded RNA (dsRNA) able to down-regulate endogenous genes, thus affecting essential vital functions via RNA interference (RNAi) in pests and pathogens, is envisioned as a more specific and environmentally-friendly alternative to traditional insecticides. However, this strategy has not been explored in medfly yet. RESULTS: Here, we screened seven candidate target genes by injecting in adult medflies gene-specific dsRNA hairpins transcribed in vitro. Several genes were significantly down-regulated, resulting in increased insect mortality compared to flies treated with a control dsRNA targeting the green fluorescent protein (GFP) complementary DNA (cDNA). Three of the dsRNAs, homologous to the beta subunit of adenosine triphosphate (ATP) synthase (ATPsynbeta), a vacuolar ATPase (V-ATPase), and the ribosomal protein S13 (RPS13), were able to halve the probability of survival in only 48 h after injection. We then produced new versions of these three dsRNAs and that of the GFP control as circular molecules in Escherichia coli using a two-self-splicing-intron-based expression system and tested them as orally-delivered insecticidal compounds against medfly adults. We observed a significant down-regulation of V-ATPase and RPS13 messenger RNAs (mRNAs) (approximately 30% and 90%, respectively) compared with the control medflies after 3 days of treatment. No significant mortality was recorded in medflies, but egg laying and hatching reduction was achieved by silencing V-ATPase and RPS13. CONCLUSION: In sum, we report the potential of dsRNA molecules as oral insecticide in medfly.